How @paparazikuansing Popularizes The Cultural Tradition of Pacu Jalur Kuantan Singingi Riau ? - Agwenda, Mezzi; Yasir; Yesicha, Chelsy (Universitas Telkom, 2024)
This research aims to analyze the content marketing strategy of the pacu jalur culturaltradition through the TikTok platform, focusing on the @paparazikuansing account. Through aqualitative and case study approach, this research explores how the @paparazikuansing accountcreates, distributes, and amplifies content related to the pacu jalur cultural tradition.The main findings show that the use of TikTok as a promotional medium is able to increase publicawareness and understanding of the pacu jalur cultural tradition. The creative content presentedmanaged to attract the attention of users from various circles, both at home and abroad. The highinteraction between the @paparazikuansing account and its followers is also an important factor inbuilding engagement and emotional connections with the audience.The implication of this research is the need to continue to pay attention to and optimize user responsesand interactions as the key to success in building engagement with audiences. The proposedrecommendations include the need for research and analysis of audience characteristics, collaborationwith influencers, and other TikTok users to expand the reach of content. It is hoped that the results ofthis study can contribute to the development of content marketing strategies for the pacu jalur culturaltradition through social media, as well as become a reference for further research in the field of contentmarketing and traditional cultural development. In conclusion, collaboration between the@paparazikuansing account, followers, and other related parties can strengthen the promotion andpreservation of the pacu jalur cultural tradition through digital platforms.